The Identity of American Catholic Higher Education: A Historical Overview - Garrett, Matthew (Catholic Education: A Journal of Inquiry and Practice, 2006)
American Catholic higher education has faced and overcome challenges, both from American higher education and Vatican officials, in its long and rich history. Georgetown College’s founding in 1789 was the first of several Catholic higher education institutions created in the late 18th and early 19th centuries. The 20th century brought the challenges of accrediting agencies and mixed communication with The Vatican, including Pope John Paul II’s (1990) Ex Corde Ecclesiae. This document attempts to clarify the nature of a Catholic institution’s identity.